Resilience of Black Sea Bass Embryos to Increased Levels of Carbon Dioxide. (9th March 2022) - Meseck, Shannon L.; Redman, Dylan H.; Mercaldo‐Allen, Renee; Clark, Paul; Rose, Julie M.; Perry, Dean M.
Abstract: After a decade of research on how embryonic fish will respond to the increased dissolved carbon dioxide (ρCO2 ) levels predicted for the next century, no uniform response to near future acidification has been observed among marine species. We exposed Black Sea Bass Centropristis striata (BSB) embryos to varied levels of ρCO2 (microatmospheres [μatm]) for 48 h during seasonal experiments conducted in 2013–2015 to compare embryonic response among multiple broodstocks. The relationship between ρCO2 concentration and hatching success was inconsistent among years, with a nonlinear, inverse relationship noted in 2014 only, explaining 13% of observed variance. Conversely, ρCO2 was a good predictor of unhatched BSB embryos after 48 h for all years combined (39%) and for 2013 (38%). The ρCO2 concentration was a good predictor of the frequency of vertebral column anomalies for individual years (2013: 40%; 2014: 12%; 2015: 38%) but not when data were pooled for all years. In 2013 and 2015, vertebral column anomalies were relatively consistent below 1, 000 μatm and were elevated above that threshold. Preliminary results suggest that BSB embryos may demonstrate resilience to future ρCO2 levels, but the results also highlight the challenges associated with drawing broad conclusions given observed variability in results obtained from different broodstocks and study years.